Risk factors for sexual dysfunction in BRCA mutation carriers after risk-reducing salpingo-oophorectomy. Issue 2 (February 2019) - Chan, Jessica L.; Senapati, Suneeta; Johnson, Lauren N.C.; DiGiovanni, Laura; Voong, Chan; Butts, Samantha F.; Domchek, Susan M.
Abstract: Objective: The aim of the study was to identify risk factors for sexual dysfunction in BRCA mutation carriers who have undergone risk-reducing salpingo-oophorectomy (RRSO). Methods: A cross-sectional study was performed. BRCA1/2 mutation carriers with and without RRSO were surveyed to determine sexual function (Female Sex Function Index [FSFI]), demographics, medical history, sleep quality, depression, and anxiety scores. Characteristics of patients with the lowest quartile of FSFI scores (<14 ± 8.8) were analyzed to identify risk factors for the most severe phenotype. Results: In the 804 women surveyed, 764 underwent RRSO. Of the 529 (69%) carriers with completed FSFI questionnaires in the RRSO cohort, sexual dysfunction was reported in 77.3%. Poor sleep ( P = 0.002), hot flashes ( P = 0.002), lack of current systemic hormone therapy (HT) use ( P = 0.002), depression ( P < 0.001), and anxiety ( P = 0.001) were associated with sexual dysfunction. In adjusted analyses, depression (adjusted odds ratio [aOR] 2.4, 95% CI, 1.4-4.1) and hot flashes (aOR 1.9, 95% CI, 1.2-3.0) remained significantly associated with sexual dysfunction. Depression was also a significant risk factor for the most severe degree of sexual dysfunction (OR 2.1, 95% CI, 1.3-3.5) and had the greatest impact on Arousal and Satisfaction domain scores of the FSFI. Current systemic HT use seemed to decrease the risk for sexual dysfunction (aOR 0.6, 95% CI, 0.4-1.0). Conclusions: Sexual dysfunction is highly prevalent in BRCA mutation carriers after RRSO. Depression seems to be a significant risk factor for sexual dysfunction in this patient population and may be under-recognized and undertreated. Patient and provider education on sexual side effects after surgery and risk factors for sexual dysfunction is necessary to decrease postoperative sexual distress. HT may be associated with improved sexual function after surgery.